PENGARUH PEMERIKSAAN PAJAK, KESADARAN, KUALITAS PELAYANAN PADA TINGKAT KEPATUHAN WAJIB PAJAK BADAN - Shinta Dewi, I Gusti Agung Cahaya; Supadmi, Ni Luh (E-Jurnal Akuntansi; Vol 9 No 2 (2014), 2014)
Examination of a fence guards to remain on the taxpayer corridor tax rules and tax authorities in carrying out their duties not only for formality activities, but also to strengthen the validity of the transaction and legal compliance with applicable law in order to remain obedient taxpayer in carrying out the rights and tax obligations purpose of this study is to determine the effect of tax audits, awareness, quality of service at the level of tax compliance in KPP Madya Agency Denpasar. This research was conducted in KPP Madya Denpasar with 100 respondents listed the Taxpayer, the random sampling method. The analysis technique used is multiple linear regression analysis. Based on the results of this study indicate that the tax audit, awareness, and service quality has a positive effect on the level of compliance of the Taxpayer by 78 percent and the remaining 22 percent is influenced by other variables that are not included in the research model.
Keywords: tax audit, awareness, quality of service